Agrarian Law Enforcement In Land Dispute Settlement - Endriyana, Riza; Santiago, Faisal; Suparno, Suparno (CV. Publikasi Indonesia, 2023)
Land ownership that is unfair to the community will offer opportunities for some parties to act undemocratically by taking land from the community. Conflict is a phenomenon that often occurs in human life, and arises from the conditions of the diversity of social systems. Conflict, no matter how it is seen, is inextricably linked with social existence. Property rights according to Article 20 paragraph (1) of the UUPA, namely hereditary, strongest, and fulfilled rights that people can own over land by considering that all land rights have a social function. The review utilizes a standardizing juridical methodology and the kind of legitimate survey is an extensive investigation of essential lawful materials, optional legitimate materials, and tertiary legitimate materials. The consequences of this exploration are the goal of land debate cases as specified in Regulation Number 51 of 1960, in Article 2 and Article 6 passage (1) letter a, that the utilization of land without consent from the legitimate individual or their lawful intermediary is a disallowed act and undermined with criminal punishments. Nonetheless, in tending to clashes and land debates that emerge, one should take a gander at it according to a few points of view while as yet focusing on equity and not hurting the two players, so it isn't just seen from the side of the inhabitant's activities yet additionally as far as the endlessly utilization of the land by the proprietor if, as far as usage, the land isn't used ideally and even appears to have been dismissed by the proprietor for roughly 15 years. Settlement of questions through consultation through intervention is followed as the way to taking care of land issues, remembering that the fundamental objective of intervention is to determine issues, apply standards or make request, yet in its execution, it should likewise be founded on broad standards